(untitled) (Thành phố Hồ Chí Minh, 2015)
This book provides you with a step-by-step guide through the three parts of the New TOEIC Reading Conprehension test. There are 20 units (14 units for Part 5 and 6, and 6 units for Part 7) with these recurring sections.
Keywords: Tiếng Anh,English language; Kỳ thi,Examinations